2021
DOI: 10.1103/physrevlett.127.215504
|View full text |Cite
|
Sign up to set email alerts
|

Unifying Description of the Vibrational Anomalies of Amorphous Materials

Abstract: The vibrational density of states DðωÞ of solids controls their thermal and transport properties. In crystals, the low-frequency modes are extended phonons distributed in frequency according to Debye's law, DðωÞ ∝ ω 2 . In amorphous solids, phonons are damped, and at low frequency DðωÞ comprises extended modes in excess over Debye's prediction, leading to the so-called boson peak in DðωÞ=ω 2 at ω bp , and quasilocalized ones. Here we show that boson peak and phonon attenuation in the Rayleigh scattering regime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 56 publications
5
12
0
Order By: Relevance
“…This phenomenon can be attributed to the shift from the small dissipation condition to the large dissipation condition [56], but further investigation is needed to verify this point. In the future, it is also interesting to describe the present results in terms of the other theoretical frameworks, including the effective medium theory or fluctuating elasticity theory [14][15][16][17][57][58][59][60], the random matrix approach [61][62][63], and other microscopic approaches [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon can be attributed to the shift from the small dissipation condition to the large dissipation condition [56], but further investigation is needed to verify this point. In the future, it is also interesting to describe the present results in terms of the other theoretical frameworks, including the effective medium theory or fluctuating elasticity theory [14][15][16][17][57][58][59][60], the random matrix approach [61][62][63], and other microscopic approaches [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…where • denotes the sample-to-sample average. The quantifier χ was discussed at length in [11,35,[54][55][56]; it has been shown to determine wave attenuation rates in the harmonic regime [55,56]. Here, we use a jackknifelike method to approximate χ, see details in [35].…”
Section: Appendix B: Observablesmentioning
confidence: 99%
“…In 2020, Chattoraj and Ciamarra demonstrated that the nonperturbative dynamic effects of attractive forces were equivalent to the activation energy at the glass transition temperature, resulting in consistent dynamic properties for various types of glassy matter, including metals, polymers, or colloids, when subjected to the same level of attractive forces [25]. Furthermore, Mahajan and Ciamarra unified the description of vibrational anomalies using elastic disorders and localised defects in glassy matter [26].…”
Section: Introductionmentioning
confidence: 99%